2012
DOI: 10.4172/2157-7145.1000146
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Profile of Snake Bite at Tertiary Care Hospital, North India

Abstract: This hospital based prospective study was conducted from September 2009 to September 2011.All the patients irrespective of age and sex, who reported with history of snake bite were included in the study. A total 169 snake bite patients, consisting of 116 (68.7%) male and 53 (31.3%) female [mean (SD) age 32±12 years] were admitted to the hospital during the study period, the ratio being 2.2:1. The majority of victims belonged to rural areas (67.5%) and most vulnerable occupation group was the people involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
30
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 10 publications
6
30
1
Order By: Relevance
“…Gaurav et al study [1]which was done in western Maharastra, showed incidence of poisonous snake bite is 50.6% while night time snake bite was 72% .So compared to this study, our study showed increased incidence of poisonous snake bite (80% vs 50.6%), increase in daytime bite (54% vs 27%). Arshad et al study [2] done at Uttar Pradesh showed results of increased Elapidae bite (15.4% vs 4.7%), increased incidence of night time bite (55.1% vs 46%) & increased mortality (8% vs 1.1%). Harshavardhana et al study [4] done at KIMS, Bangalore revealed similar incidence of Viperidae bite (70% vs 73%) with mortality of 4% (vs 1.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Gaurav et al study [1]which was done in western Maharastra, showed incidence of poisonous snake bite is 50.6% while night time snake bite was 72% .So compared to this study, our study showed increased incidence of poisonous snake bite (80% vs 50.6%), increase in daytime bite (54% vs 27%). Arshad et al study [2] done at Uttar Pradesh showed results of increased Elapidae bite (15.4% vs 4.7%), increased incidence of night time bite (55.1% vs 46%) & increased mortality (8% vs 1.1%). Harshavardhana et al study [4] done at KIMS, Bangalore revealed similar incidence of Viperidae bite (70% vs 73%) with mortality of 4% (vs 1.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians have for a long time witnessed the tragedy of injury in Sri Lankan soil, disability, and death from snake bite that is a daily occurrence [1]. To many people living in North Central Province, including some of the Sri Lankans poorest communities, snake bite is an ever present occupational risk and environmental hazard, an additional penalty of poverty.…”
Section: Mini Reviewmentioning
confidence: 99%
“…Like sand fly disease currently emerging, dengue, tuberculosis, and parasitic diseases, the risk of snake bite is always present. Unlike many of other community based health risks, Sri Lanka is having high percentage of human suffering caused by snake bite remains unrecognized, and even neglected by development agencies and even government [1].…”
Section: Mini Reviewmentioning
confidence: 99%
“…Unlike many of other community based health risks, Sri Lanka is having high percentage of human suffering caused by snake bite remains unrecognized, and even neglected by development agencies and even government. 1 In the tropical developing country like Sri Lanka where snake bites occur most commonly, there are few reliable incidence data. 2 Most of the familiar methods for snake bite treatment, both western and "traditional/ indigenous"; have been found to result in more harm (risk) than good (benefit).…”
mentioning
confidence: 99%
“…Cobra/Naya (Naja naja); Common krait/ Magamaruwa, Thel Karawala Clinicians have for a long time witnessed the tragedy of injury in Sri Lankan soil, disability, and death from snake bite that is a daily occurrence. 1 To many people living in North Central Province, including some of the Sri Lankans poorest communities, snake bite is an ever present occupational risk and environmental hazard, an additional penalty of poverty. Like sand fly disease currently emerging, dengue, tuberculosis, and parasitic diseases, the risk of snake bite is always present.…”
mentioning
confidence: 99%